Autosomal recessive corneal endothelial dystrophy (CHED2) is associated with mutations in SLC4A11. Issue 1 (6th July 2006) - Jiao, Xiaodong; Sultana, Afia; Garg, Prashant; Ramamurthy, Balasubramanya; Vemuganti, Geeta K; Gangopadhyay, Nibaran; Hejtmancik, J Fielding; Kannabiran, Chitra
Abstract : Objective: To map and identify the gene for autosomal recessive congenital hereditary endothelial dystrophy (CHED2, OMIM 217700), a disorder characterised by diffuse bilateral corneal clouding that may lead to visual impairment and requiring corneal transplantation. Methods: Members of 16 families with autosomal recessive CHED were genotyped for 13 microsatellite markers at the CHED2 locus on chromosome 20p13-12. Two-point linkage analysis was carried out using the FASTLINK version of the MLINK program. Mutation screening was carried out by amplification of exons and flanking regions by polymerase chain reaction, followed by direct automated sequencing. Results: Linkage and haplotype analysis placed the disease locus within a 2.2 cM (1.3 Mb) interval flanked by D20S198 and D20S889, including SLC4A11. The maximum limit of detection score of 11.1 was obtained with D20S117 at θ = 0. Sequencing of SLC4A11 showed homozygotic mutations in affected members from 12 of 16 families. Conclusion: These results confirm that mutations in the SLC4A11 gene cause autosomal recessive CHED.